畢氏定理 證明 3

\begin{equation}讓\mathrm{BH}=\mathrm{BC}=\mathrm{a}且讓\mathrm{BD}\perp\mathrm{CH}\end{equation}

\begin{equation}則\angle\mathrm{DBH}=\angle\mathrm{DBC}\end{equation}

\begin{equation}\therefore\triangle\mathrm{DBC}\cong\triangle\mathrm{DBH}\Rightarrow\angle\mathrm{DHB}=\mathrm{90}^\circ,\mathrm{DC}=\mathrm{DH}=\mathrm{x}\end{equation}

\begin{equation}\because\triangle\mathrm{ABC}\sim\triangle\mathrm{ADH}\end{equation}

\begin{equation}\therefore\mathrm{a}:\mathrm{x}=\mathrm{b}:(\mathrm{c}-\mathrm{a})\end{equation}

\begin{equation}\Rightarrow\mathrm{ac}-\mathrm{bx}=\mathrm{a}^2\cdots\cdots(\mathrm{1})\end{equation}

\begin{equation}\therefore\mathrm{b}:(\mathrm{c}-\mathrm{a})=\mathrm{c}:(\mathrm{b}-\mathrm{x})\end{equation}

\begin{equation}\Rightarrow\mathrm{ac}-\mathrm{bx}+\mathrm{b}^2=\mathrm{c}^2\cdots\cdots(\mathrm{2})\end{equation}

\begin{equation}將(\mathrm{1})代入(\mathrm{2})可以即可得到\end{equation}

\begin{equation}\Rightarrow\mathrm{a}^2+\mathrm{b}^2=\mathrm{c}^2\end{equation}

Reference:

1. Elisha S. Loomis (1935): « The Pythagorean Proposition ». p. 43.

發佈留言